Prevalence of ear, nose and throat disorders in children at government district hospital Vizianagaram - Raju, M. Rama Krishnam; Fareeduddin, M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Ear, nose and throat (ENT) problems are very common among the children, there is a lack of data on paediatric otorhinolaryngology from various Indian populations. This study was conducted to determine the hospital based prevalence of ENT disorders in paediatric population. Methods: A record based, retrospective study conducted at government district Hospital, Vizianagaram, Andhra Pradesh, India. 1818 children between the ages of 0-15, attending the ENT department in our hospital were included in the study. General demographic details taken, and examination for common ENT complaints and disorders was taken for all patients. Otoscopy for ear examination for ear perforation and ear discharges. Anterior rhinoscopy for nasal discharge and airway obstruction. Throat examination was performed for any sign of tonsillitis or pharyngitis and adenoids. Results: ENT diseases in our study population were found to be more common among male children (57.97%). Majority of the paediatric patients belonged to age group 5-14 years (65.7%), were from lower socioeconomic status (57.53%), living in nuclear family (62.81%) and had illiterate mothers (68.5%). Diseases of ear system (44%) were the most common group of ENT problems among the paediatric population, followed by nasal (30.9%) and throat (25.1%) disorders. The most common ENT disorders were otitis media (22.1%), tonsillitis (11.66%). Conclusions: Our study provides basic information of the prevalent disorders in ENT in our area suggests that otitis media, tonsillitis and rhinitis are the most common otorhinolaryngological problems in paediatric population visiting the ENT Department of this hospital and contribute significantly to paediatric morbidity.